2011
DOI: 10.1016/j.lfs.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

L-histidine sensing by calcium sensing receptor inhibits voltage-dependent calcium channel activity and insulin secretion in β-cells

Abstract: Aims-Our goal was to test the hypothesis that the histidine-induced activation of calcium sensing receptor (CaR) can regulate calcium channel activity of L-type voltage dependent calcium channel (VDCC) due to increased spatial interaction between CaR and VDCC in β-cells and thus modulate glucose-induced insulin secretion.Main methods-Rat insulinoma (RINr1046-38) insulin-producing β-cells were cultured in RPMI-1640 medium on 25 mm diameter glass coverslips in six-well culture plates in a 5% CO 2 incubator at 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
(72 reference statements)
2
5
0
Order By: Relevance
“…Yamamura and colleagues reported that Bay K8644 can directly activate CaR, increasing CaR‐mediated cytosolic Ca 2+ concentration. Studies also describe reciprocal relationship between CaR and LTCC due to increased spatial interaction, or change of extracellular calcium . Our results agreed with these finds because Bay K8644 directly increased cytosolic Ca 2+ in Rgs12 f/f OPCs; however, whether CaR involved in cytosolic Ca 2+ restraint after Rgs12 deletion is uncharted in the current study, as well as the deletion effect on LTCC subunits, and more studies are needed.…”
Section: Discussionsupporting
confidence: 89%
“…Yamamura and colleagues reported that Bay K8644 can directly activate CaR, increasing CaR‐mediated cytosolic Ca 2+ concentration. Studies also describe reciprocal relationship between CaR and LTCC due to increased spatial interaction, or change of extracellular calcium . Our results agreed with these finds because Bay K8644 directly increased cytosolic Ca 2+ in Rgs12 f/f OPCs; however, whether CaR involved in cytosolic Ca 2+ restraint after Rgs12 deletion is uncharted in the current study, as well as the deletion effect on LTCC subunits, and more studies are needed.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, patients who were homozygous for the S986 minor allele had elevations in serum glucose, and this highlights a potential role for the CaSR as a regulator of systemic glucose homeostasis. Indeed, this would be consistent with the reported expression of the CaSR in pancreatic islet beta-cells and that CaSR activation by extracellular calcium or calcimimetic drugs in isolated islets can stimulate beta-cell activity and insulin secretion [ 33 35 ]. In addition, the CaSR is expressed and functionally active in adipocytes [ 36 ], and may potentially regulate the peripheral actions of insulin, as highlighted by the finding of an association with the A986S CASR polymorphism and insulin resistance in patients with the polycystic ovarian syndrome [ 37 ].…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the CaSR has been detected in pancreatic islet beta‐cells, with evidence suggesting it modulates insulin release (Squires et al ., ; Leech and Habener, ; Gray et al ., ; Parkash and Asotra, ).…”
Section: Modulation Of Macronutrient Digestion Absorption Nutrient mentioning
confidence: 99%